Development of Micro, Small and Medium Enterprises Rattan Woven Crafts in Central Kalimantan, Indonesia - Iin Nurbudiyani; Sonedi Sonedi; Endang Sri Suyati; Mohammad Rizki Fadhil Pratama (Anterior Jurnal, 2019)
This study discusses the development of small and medium micro enterprises (MSMEs) in Central Kalimantan with rattan woven craft industries being used as samples to represent other MSME sectors. The purpose of this study is to describe the improvement in the performance and strategy of the MSME group covering various aspects such as job training, capital support, equipment/technology assistance, and access to information and communication. The findings of this study indicate that the development of MSMEs carried out by regional governments in Central Kalimantan has gone in the right direction, with several factors still making improvements possible. Support in the form of training should be conducted regularly and scheduled with the topic of continuous training and productive participants. Aid in the form of equipment requires periodic evaluations, such as a reward-punishment system for business groups that have received various support to ensure the support provided is on target. Another strategy is to form the centre of the MSME industry in the Capital of the Province, to facilitate the access of tourists who just want to visit looking for typical Central Kalimantan souvenirs. The easiest way to do this now is to implement a movement of love for standard Central Kalimantan handicraft products to be displayed in various offices, offices, and government agencies as well as different infrastructure and public facilities.